Implementing Differentiated Learning in the Merdeka Curriculum at Upper Elementary Level: Teachers’ Constraints and Adaptive Strategies - Muhammad Sulthon Fadil; Iik Nurulpaik (Research, Training and Philanthropy Institution Natural Aceh, 2026)
Differentiated learning constitutes a fundamental component of the Independent Curriculum that realizes responsive instruction toward student diversity. Its implementation in grade VI poses complex challenges that require adaptive strategies. This study analyzes the constraints and strategies teachers employ in implementing differentiated learning within the Independent Curriculum for grade VI in an elementary school. This qualitative descriptive research involved two grade VI teachers, the principal, and the curriculum coordinator at SDN Serang 20, Serang City. Data were collected through interviews, classroom observations, and document analysis. Findings indicate that differentiation practices predominantly occur in the learning process through flexible grouping and individual mentoring, while content and product differentiation remain limited. Main constraints include non-operational conceptual understanding, limited planning time, high student ability heterogeneity, infrastructure limitations, and administrative burden. Teachers develop adaptive strategies through continuous independent learning, collaborative learning community, simplified teaching modules, flexible grouping, intensive individual mentoring, and creativity in creating simple learning media. Institutional support through learning communities and collaborative leadership is a key success factor.